MAT1-1-3, a Mating Type Gene in the Villosiclava virens, Is Required for Fruiting Bodies and Sclerotia Formation, Asexual Development and Pathogenicity - Yong, Mingli; Yu, Junjie; Pan, Xiayan; Yu, Mina; Cao, Huijuan; Qi, Zhongqiang; Du, Yan; Zhang, Rongsheng; Song, Tianqiao; Yin, Xiaole; Chen, Zhiyi; Liu, Wende; et al. (Frontiers in Microbiology, 2020)
Villosiclava virens is the prevalent causative pathogen of rice false smut, a destructive rice disease. Mating-type genes play a vital role in the evolution of mating systems in fungi. Some fungi have lost MAT1-1-3, one of the mating-type genes, during evolution, whereas others still retain MAT1-1-3. However, how MAT1-1-3 regulates the sexual development of heterothallic V. virens remains unknown. Here, we generated the MAT1-1-3 mutants, which exhibited defects in vegetative growth, stress response, pathogenicity, sclerotia formation and fruiting body maturation. An artificial outcrossing inoculation assay showed that the mat1-1-3 mutant was unable to produce sclerotia. Unexpectedly, the mat1-1-3 mutant could form immature fruiting bodies without mating on potato sucrose agar medium (PSA) compared with the wild-type strain, most likely by activating the truncated MAT1-2-1 transcription to regulate the sexual development. Moreover, RNA-seq data showed that knockout of MAT1-1-3 results in misregulation of a subset of genes involved in sexual development, MAPK signaling, cell wall integrity, autophagy, epigenetic modification, and transcriptional regulation. Collectively, this study reveals that MAT1-1-3 is required for asexual and sexual development, and pathogenicity of V. virens, thereby provides new insights into the function of mating-type genes in the fungi life cycle and infection process.